Descolonizar a história da África e da cultura afro-brasileira : por um currículo negro afrorreferenciado e pluriversal - Luzia, Adriana Germana (2022)
The main subject of this production is the Teaching of African History and Afro-Brazilian Culture.Its objectives are: 1) to historically understand the black social movements in the post-abolition period and the struggles for the introduction of the History of Africa and black people in Brazil in school curriculum; 2) to discuss Law 10.639/2003 as a result historical struggles by black social movements for an anti-racist and transformative education; 3) to analyze the History of Africa and Afro-Brazilian Culture in the NationalCommon Curriculum Base (initials in Portuguese BNCC). The research has as problematic the way the African History and Afro-Brazilian culture is present in brazilian educational legislation. At first, we notice the presence of the subject in educational legislation, mainly from Law 10.639/2003 and the National Curriculum Guidelines for the Education of Ethnic-Racial Relations, as well as objects of knowledge, skills and competencies related to the History of Africa and Afro-Brazilian Culture in the text of the Common National Curriculum Base (BNCC). However, the more detailed analysis allows identifying the maintenance of an understanding of the subject from Eurocentric epistemological paradigms. It seeks, therefore, to point out didactic-pedagogical approaches that overcome the epistemological view of the "unique model" of Eurocentrism, with a viewto a pluriversal approach in the production of knowledge. The reflection is guided by debates on decolonization and decoloniality (Bernardino-Costa; Maldonado-Torres; Grosfoguel; 2019; Anibal Quijano, 2005), etc. We used the elaborations of black intellectuals from different times and places: AfroBrazilians such as: Abdias Nascimento; Beatriz Nascimento; Guerreiro Ramos; Munanga Kabengele; Sueli Ram; Nilma Lino Gomes; Renato Noguera. African intellectuals: Cheikh Anta Diop; Joseph Ki-Zerbo; Mogobe Ramose; Chinua Achebe; Chimamanda Ngozi Adichie, from the United States and the Caribbean: bell hooks; Molefi Kete Asante; Frantz Fanon; AiméCésaire; Carlos Moore; among others. And based on this reference, the Educational Product elaborated was a proposal of a continuing education course for teachers on the teaching of History of Africa and AfroBrazilian Culture of a afro-referenced and pluriversal approach, centered on the locus of black enunciation afrodiasporic; fromthe point of view and from the "legitimately African" perspective, from the historical experiences of Africans themselves and their epistemologies, in which all perspectivesmust be valid, an intercultural exercise.